An introduction to linguistic synergetics - Dombrovan, Tetiana (Cambridge Scholars Publishing, 2018)
The book provides an introduction to some basic concepts of linguistic synergetics, viewed here as a new multidisciplinary research approach to language studies. It also advances diachronic linguosynergetics, focusing on principles and mechanisms of language change and development, and employing the methodological integrity of philosophy, linguistics and synergetics. Diachronic linguosynergetics endeavours to capture language in a state of change, when a language system follows a non-linear path, through numerous fluctuations and dissipation, leading out of chaos to order and stability. The bo.